1999
DOI: 10.1007/s004360050519
|View full text |Cite
|
Sign up to set email alerts
|

Flow cytometry analysis of drug transport mechanisms in Haemonchus contortus susceptible or resistant to anthelmintics

Abstract: The role of membrane drug-transport mechanisms in resistance to anthelmintics was examined using a flow cytometry method. This method was adapted from assays developed for the study of similar mechanisms in tumor cells. Rhodamine 123, a P-glycoprotein transport probe, associated with the reversal agent verapamil gave a significantly higher level of green fluorescence in Haemonchus contortus-resistant eggs as compared with that of susceptible eggs. In the same way, verapamilbodipy, a new fluorescent probe for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
34
0
3

Year Published

2000
2000
2018
2018

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 17 publications
3
34
0
3
Order By: Relevance
“…A similar stepwise selection of BZ resistance also occurs in some Trichostrongylus colubriformis and Ostertagia circumcincta populations (45,68). Furthermore, Kerboeuf et al (84) recently provided indirect evidence that P-glycoproteins (P-gp) also play a role in BZ resistance in H. contortus. P-gp are involved in multidrug resistance in mammalian tumor cells, Leishmania, and Plasmodium and in resistance to toxic compounds in C. elegans.…”
Section: Mechanisms Of Drug Resistancementioning
confidence: 91%
See 1 more Smart Citation
“…A similar stepwise selection of BZ resistance also occurs in some Trichostrongylus colubriformis and Ostertagia circumcincta populations (45,68). Furthermore, Kerboeuf et al (84) recently provided indirect evidence that P-glycoproteins (P-gp) also play a role in BZ resistance in H. contortus. P-gp are involved in multidrug resistance in mammalian tumor cells, Leishmania, and Plasmodium and in resistance to toxic compounds in C. elegans.…”
Section: Mechanisms Of Drug Resistancementioning
confidence: 91%
“…Since it has been shown that P-gp plays a role in resistance to BZ and IVM in H. contortus (12,84,158), it can be expected that the same resistance mechanism might develop in many other helminths, including O. volvulus.…”
Section: Detection Of Drug Resistancementioning
confidence: 99%
“…When MXR inhibitors were used, an in crease of the fluorescence was noted, as previously re ported for other species (Cornwall et al 1995, Kerboeuf et al 1999, Hamdoun et al 2004, Marin et al 2004, Zaja et al 2006). …”
Section: Rb Incorporationmentioning
confidence: 63%
“…This indirect measurement method has been used for a long time and is still used for the detection of Pgplike and MRP-like activities (Neyfakh 1988, Kerboeuf et al 1999, Hamdoun et al 2004, Lüders et al 2009), as well as for the detection of MXR/MDR activity (Holland Toomey & Epel 1993, Cornwall et al 1995, Zaja et al 2006, Caminada et al 2008. The CsA and Ver are not as specific as first claimed 10 yr ago.…”
Section: Response Comparisonmentioning
confidence: 99%
“…Active Pgp was later detected in the gastrointestinal nematode Haemonchus contortus (31) by use of UIC2 monoclonal antibody (MAb), which specifically binds the active form of the protein (40). The role of Pgp in xenobiotic transport has also been demonstrated in this nematode by use of rhodamine 123 (R123) (29) as a specific Pgp substrate (44).…”
mentioning
confidence: 99%